만주어 격어미 수-比）의 통人］', 의미 특성 연구 한국어. 몽골어와의 비교를 중심으로-느: Meaning feature ofsuffix {-de} of Manchu language, compared to Korean and Mongolian - Т.Otgontuul (Acta Mongolica, 2008)
This paper is to study syntactic similarities and differences among Manchurian locative/dative affix {-de}, Mongolian and Korean locative/dative affixes. This study is to compare the Chongo nogoltae a teaching material of Manchurian language written in Korean in the 18th century with a printed Manchurian material at that time. The Korean material which is compared with Manchurian language is diachronically a modern Korean (from the beginning ofthe 17th century to the end of the 19th century). Manchurian language, however, had been used until the 17th or 18th century, and no longer used nowaday. It brings much difficulty to study systematic case affixes because of the lack ofspoken Manchurian. Instead we can find perfectly written classic Manchurian materials, so I try to find systematic characteristics of Manchurian case affixes based on the study ofsystematic Korean and Mongolian case affixes. This study shows that the locative/dative case affixes of Korean. Manchurian and Mongolian which belong to Altaic language are almost same in the meaning and function. The affixes denote originally locative/dative meaning and function, but sometimes they represent other case. In a morphological level the Manchurian and Mongolian locative/dative {-da/-de’} and {k-ta/-te} are originally same affixes, but they are totally different forms from Korean. In a semantic level the Manchurian {-de} had a characteristic ofrepresenting instrumental, ablative, appositive, accusative, reflexive-possessive as well as the meaning of locative/dative affixes in Mongolian. The reason is that the locative/ dative affixes {-da/-de’ and '-ta/-te} are old forms in Manchurian and Mongolian and there was a case they denoted accusative, instrumental, ablative and appositive cases in both languages. The {-de} affix, however, came to represent a locative/ dative case later from a diachronical point of view.